25-year follow-up of treated and not-treated adolescents after the Spitak earthquake: course and predictors of PTSD and depression. Issue 6 (14th April 2021) - Goenjian, Armen K.; Steinberg, Alan M.; Walling, David; Bishop, Sheryl; Karayan, Ida; Pynoos, Robert
Abstract: Background: There is a paucity of long-term prospective disaster studies of the psychological sequelae among survivors. Methods: At 1½ and 25 years after the Spitak earthquake, 142 early adolescents from two cities were assessed: Gumri (moderate–severe exposure) and Spitak (very severe exposure). The Gumri group included treated and not-treated subjects, while the Spitak group included not-treated subjects. Instruments included: DSM-III-R PTSD-Reaction Index (PTSD-RI); DSM-5 PTSD-Checklist (PCL); Depression Self-Rating Scale (DSRS); and Center for Epidemiological Studies-Depression Scale (CES-D). Results: (1) Between 1½ and 25 years, PTSD rates and mean scores decreased significantly in the three groups (over 50%). However, at 25 years 9.1–22.4% met DSM-5 PTSD criteria. (2) At 1½ years, the Spitak group had higher PTSD-RI ( p < 0.001) and DSRS scores ( p < 0.001) compared to the Gumri-not-treated group. At 25 years, the Spitak group that had experienced fewer post-earthquake adversities ( p < 0.03), had a greater decrease in PTSD-RI scores ( p < 0.02), and lower CES-D scores ( p < 0.01). (3) Before treatment, PTSD-RI and DSRS scores did not differ between the Gumri-treated and not-treated groups. At 25-years, the Gumri-treated group showed a greater decrease in PTSD-RI scores ( p < 0.03), and lower mean PTSD-RI ( p < 0.02), PCL ( p < 0.02), and CES-D ( p < 0.01) scores. (4) Predictors of PTSD symptom severity at 25-years included: home destruction, treatment, social support, post-earthquake adversities, and chronic medical illnesses. Conclusion: Post-disaster PTSD and depressive symptoms can persist for decades. Trauma-focused treatment, alleviation of post-disaster adversities, improving the social ecology, and monitoring for chronic medical illnesses are essential components of recovery programs.